Kepemimpinan Kepala Sekolah Di SD Negeri 3 Sumberagung Kecamatan Ngaringan Grobogan - Jumaryati, Jumaryati; , Prof. Dr. Bambang SumardjokoM.Pd; , Dr. Achmad Fathoni, M.Pd (2017)
The purpose of this study is to 1) describe a model of school leadership, 2) to describe the principal's role, 3) to describe the constraints faced by principals. This research type is qualitative and ethnographic design uses. Takes place at SDN 3 Sumberagung Ngaringan Subdistrict Grobogan. Methods of data collection using in-depth interviews, observation, and documentation. Analysis of data starting from data reduction, a data display, and conclusion drawing / verification. Test the validity of the data using a triangulation of sources and techniques. The results of this study are (1) the principal's leadership style SDN 3 Sumberagung using situasionaal leadership style that is because of the leadership of participation, facilitative and delegates. Leadership style demonstrated by their participation reciprocal communication between the leader and teachers. Style facilitative leadership presented upon principals try to fulfill every wish subordinate. Leadership styles delegation indicated at the time the principal gives full authority and responsibility to his subordinates. (2) The principal of SDN 3 Sumberagung in running his leadership has been carrying out its roles and functions as an educator, Manager, Administrator, Supervisor, Leader, innovator and motivator with good success. (3) The principal of SD Negeri 3 Sumberagung coordinate with all citizens of good school teachers, committee and parents to overcome the constraints that exist. All obstacles can be overcome through good communication between the principal with the school community. Keywords: leadership, leadership models, the quality of schools